Attitudes of police personnel towards their job - Ishak, Salma; Musa, Mohd Makzan (Universiti Utara Malaysia, 1996)
The objective of the study was to examine work attitudes among police personnel and its relationship with selected demographic variables, personal characteristics,and work-related factors. A sample consisting of 182 police personnel from 4 police headquarters in Wilayah Persekutuan responded to the questionnaire. Results revealed that, in general, police personnel in this study showed a fairly positive attitude towards their job, a positive perception of the support and concern from the police force, and were generally not under great mental strain. Significant positive correlations were obtained for age, personal well-being, length of service,and perception of support from the police force with work satisfaction. Significant differences were also observed for work satisfaction on the basis of their rank, and the police station as well as the division where they were attached at the time of the study